Association between loneliness and incident atrial fibrillation across different genetic predisposition: findings from the UK Biobank - Zechen Liu; Yanjun Song; Shanshan Shi; Zhihao Zheng; Weihua Song; Wenjia Zhang; Kefei Dou (European Journal of Medical Research)
Abstract Background Loneliness has garnered significant attention globally, with extensive exploration of its association with cardiovascular disease. However, a notable research gap persists concerning loneliness and its potential link to atrial fibrillation (AF). Methods This prospective cohort study utilized data from the UK Biobank (UKB), encompassing 441,056 participants. Loneliness was assessed through self-reported questionnaires gauging feelings of isolation and willingness to confide. AF diagnoses were ascertained using hospitalization records and cause-of-death registry data. The association between loneliness and AF risk was analyzed through multivariable Cox proportional hazard models. Results Over a median follow-up period of 13.9 years, 25,386 AF cases were identified. In comparison to individuals without reported loneliness, those in the loneliness group exhibited a significantly higher risk of AF (loneliness vs. non-loneliness: hazard ratio [HR]: 1.11, 95% confidence interval [CI] 1.07–1.16). Subgroup analysis revealed that the association between loneliness and increased AF risk was significant solely in individuals without heart valve disease (HR: 1.12, 95% CI 1.07–1.16). Additionally, significant associations between loneliness and heightened AF risk were noted across strata of genetic susceptibility to AF, with no observable impact on these associations by genetic susceptibility (P for interaction = 0.070). Conclusions This study establishes a robust association between loneliness and an elevated long-term risk of AF. Notably, this association is particularly pronounced in individuals without valvular disease and does not appear to be influenced by genetic predisposition to AF.